1996
DOI: 10.1080/096582196388898
|View full text |Cite
|
Sign up to set email alerts
|

Remembering the Earthquake: Direct Experience vs. Hearing the News

Abstract: Three groups of informants--two in California, one in Atlanta--recalled their experiences of the 1989 Loma Prieta earthquake shortly after the event and again 11/2 years later. The Californians' recalls of their own earthquake experiences were virtually perfect. Even their recalls of hearing the news of an earthquake-related event were very good: much higher than Atlantan recalls of hearing about the quake itself. Atlantans who had relatives in the affected area remembered significantly more than those who did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
145
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(158 citation statements)
references
References 21 publications
9
145
4
Order By: Relevance
“…Although memory for the context of occurrence may undergo distortion over time (see, e.g., Neisser et al, 1996), the intensity of the initially experienced emotional reaction is directly related to recall accuracy and confidence (e.g., Conway et al, 1994). 5 Binding theory explains enhanced memory for flashbulb events and their context of occurrence in the same way as enhanced memory for taboo words and their consistently linked colors in Experiments 1-3: Emotional events strongly engage the binding mechanisms for linking the event to its context, including the time, place, and manner of learning about it and other events ongoing at the time-for example, who else was present.…”
Section: Naturalistic Observations Consistent With Binding Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Although memory for the context of occurrence may undergo distortion over time (see, e.g., Neisser et al, 1996), the intensity of the initially experienced emotional reaction is directly related to recall accuracy and confidence (e.g., Conway et al, 1994). 5 Binding theory explains enhanced memory for flashbulb events and their context of occurrence in the same way as enhanced memory for taboo words and their consistently linked colors in Experiments 1-3: Emotional events strongly engage the binding mechanisms for linking the event to its context, including the time, place, and manner of learning about it and other events ongoing at the time-for example, who else was present.…”
Section: Naturalistic Observations Consistent With Binding Theorymentioning
confidence: 99%
“…An example is flashbulb memories, which have two defining characteristics. One is especially high accuracy and confidence in the recall of emotionally arousing events, such as the deaths of Princess Diana, John F. Kennedy, and Martin Luther King, Jr., the San Francisco earthquake, the space shuttle Challenger explosion, the Hillsborough stadium disaster, and the verdict announcement in the O. J. Simpson trial (e.g., Conway et al, 1994;Neisser et al, 1996).…”
Section: Naturalistic Observations Consistent With Binding Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly, researchers have failed to find a consistent relation between four of these variables and FBM consistency (for a review, see Talarico & Rubin, 2009). The one exception is personal significance (Bohn & Berntsen, 2007;Conway et al, 1994;Curci, Luminet, Finkenauer, & Gisle, 2001;Er, 2003;Neisser et al, 1996;Niedźwieńska, 2003;Otani et al, 2005), and the related constructs of importance to social identity (see Berntsen, 2009) and to personal identity (as, for instance, measured by the Centrality of Event Scale; CES, Berntsen & Rubin, 2006 As for memory for the public events that elicit FBMs (i.e., event memory), although the literature is much smaller, the results have been more consistent (for studies on event memory, see, for example, Bohannon, 1988;Coluccia, Bianco, & Brandimonte, 2010;Curci & Luminet, 2006;Hirst et al, 2009;Shapiro, 2006;Smith, Bibi, & Sheard, 2003;Tekcan, Ece, Gülgöz, & Er, 2003). In addition to personal significance or importance to one's identity (Coluccia et al, 2010;Curci & Luminet, 2006;Tekcan et al, 2003), emotional intensity (Bohannon, 1988;Coluccia et al, 2010;Smith et al, 2003) and rehearsal (Hirst et al, 2009;Shapiro, 2006) have also been found to be positively related to event memory accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in forensic and cognitive psychology, gauging the accuracy and consistency of eyewitness reports of emotional events, have shown that arousal enhances remembering of situations (Christianson, 1992;van Giezen et al, 2005;Hulse et al, 2007). In the case of natural disasters, emotional involvement and exposure to an earthquake has been associated with improved recall of the event itself (Neisser, 1996), in comparison only to seeing the event on television (Er, 2000). Furthermore, disaster-related interviews about Hurricane Hugo 4 (1989) and Hurricane Andrew (1992) have revealed remarkable memory stability over time (Norris and Kaniasty, 1992;Bahrick et al, 1998;Fivush et al, 2004).…”
mentioning
confidence: 99%